Efektivitas Media Puzdik (Puzzle Tabel Periodik) Berbasis Gamifikasi Terhadap Pemahaman IPA di MTs.N 1 Nganjuk - Siti Hikmatun Nisa'; Ummiy Fauziyah Laili; Puspoko Ponco Ratno; Riska Yulistiani (Lembaga Bale Literasi, 2025)
This study examines the issue of students' low understanding of chemical elements at the MTsN 1 Nganjuk, which is influenced by the abstract nature of the material and the lack of interactivity in its presentation. The primary objective of this research is to evaluate the effectiveness of PUZDIK (Periodic Table Puzzle) as a gamification-based learning medium in enhancing students’ conceptual understanding in science. The study employed a quantitative approach with a quasi-experimental method using a one-group pretest-posttest design. The research involved 33 eighth-grade students from MTsN 1 Nganjuk, selected through purposive sampling. The instruments used were essay-type questions for both pretest and posttest, analyzed using the Wilcoxon Signed Ranks Test and N-Gain calculation. The results showed a significant improvement between pretest and posttest scores, with a significance value of 0.000 (< 0.05), and N-Gain scores categorized as high (≥ 0.82), with an average increase reaching 100%. These findings indicate that the PUZDIK media is effective in strengthening students’ conceptual understanding in science. The implication of this study highlights the importance of developing learning media that integrate visual elements and gamification to foster a more engaging, active, and meaningful learning experience.